Differences in glycosylation patterns of closely related murine leukemia viruses - Rosner, Marsha Rich (1980)
The nature of the carbohydrate chains in the major envelope glycoprotein of murine leukemia virus, gp70, and its cellular precursor has been investigated. A difference in the oligosaccharide composition of gp70 from an ecotropic murine leukemia virus (Akv) and three recombinant dual-tropic viruses [mink cell focus-inducing viruses (MCFs)] derived from Akv was demonstrated. Glycosidase digestion and gel filtration were utilized to identify the two classes of N-asparagine-linked oligosaccharides, high-mannose and complex. The gp70 of the ecotropic virus contained only N-linked oligosaccharides of the complex type. In contrast, the gp70s of the dual-tropic viruses contained both high-mannose and complex oligosaccharides. Analysis of gp70 glycopeptides from an MCF-related xenotropic virus showed an elution profile similar, but not identical, to profiles of the MCFs. The gp70 precursors isolated from cells infected with Akv or MCF virus contained N-linked oligosaccharides that were exclusively of the high-mannose type. Comparison of the high-mannose oligosaccharides of the MCF gp70 precursors with those of the corresponding gp70s indicated that very little further processing of the high-mannose residues in the gp70s had occurred. The presence of the high-mannose oligosaccharides in the envelope glycoprotein of the dual-tropic viruses results from altered carbohydrate processing. The conservation of this altered carbohydrate pattern in a number of hosts and under various conditions of growth suggests that the viral protein structure is the primary factor in determining the different mode of glycosylation of the MCF gp70s. Thus, these viral glycoproteins provide an important model system for studying the relationship between protein structure and patterns of glycosylation.